Artikel Review: Produksi dan Aplikasi α-Amilase Bakteri Psikrofilik di Bidang Pangan - Nurjasmi, Reni; Aprilia, Sarah; Ruhimat, Riki; Rahmatullah, Rifki (JURNAL PERTANIAN, 2025)
Psychrophilic bacteria have been widely found in extreme low-temperature environments such as the Arctic and Antarctic oceans and glacial lakes. Some of these bacteria possess the hydrolytic enzyme α-amylase, which functions to hydrolyze starch into simple sugars such as maltose, maltotriose, and glucose. The structure of psychrophilic α-amylase is highly flexible due to reduced hydrophobic interactions and an increased number of hydrophilic residues. This unique structure allows the enzyme to function optimally at low temperatures, specifically 0–20 °C. High-quality enzymes can be obtained through integrated production stages, including the isolation of psychrophilic bacteria, low-temperature fermentation, and stepwise purification. Response Surface Methodology is often employed to achieve high yet economical enzyme yields. The enzyme isolated from psychrophilic bacteria is purified through ammonium sulfate precipitation, dialysis, and several chromatographic techniques performed sequentially to obtain a pure enzyme ready for characterization. Biochemical characterization reveals high enzyme activity at low temperatures, an optimal pH range of 6.5–8.0, and a strong dependence on calcium ions to maintain structural stability. Kinetic analysis shows that psychrophilic α-amylase has a low Michaelis constant (Km), indicating high substrate affinity that enables optimal performance even when substrate availability is limited. These advantages are widely utilized in various fields, particularly the food-processing industry, such as syrup production, baking, fermented beverages, and frozen-food processing. The ability of α-amylase to function at low temperatures provides significant benefits for food processing because it reduces energy requirements, thereby lowering production costs. The application of psychrophilic α-amylase also offers a promising solution for achieving environmentally friendly food-processing industries.